Elsevier's banking dictionary in six languages : English-American, French, Italian, Spanish, Dutch, and German - Ricci, Julio (Amsterdam ; New York : Elsevier Pub. Co., 1966)
In this dictionary, languages have been arranged in Anglo-Saxon, Latin and Germanic groups. There is, for each language, an alphabetical list of words, referring to the corresponding numbers in the basic table.
ne 02/09/2021
Ref.
Keywords: Banks and banking; English language